Faktor-Faktor yang Mempengaruhi Intensi Kewirausahaan - Rustiyaningsih, Sri (Widya Warta, 2013)
This study aimed to examine the effect of need for achievement, self-efficacy, readiness of  instrumentation, gender, age, and parental occupational background on entrepreneurial intentions. This study  tested a  hypothesis - causal relationship among variables. The data used were primary data obtained by directly distributing questionnaires to the respondents namely, the students of the Faculty of Economics who were still active in college. Hypothesis testing  made use of multiple regression analysis and independent sample T-test. The analysis showed that the need for achievement had no effect toward entrepreneurial intentions. While,  self-efficacy and instrumentation readiness had significant effect toward entrepreneurial intentions. There was no difference of  entrepreneurial intentions between male students dan female students. There was also no difference of entrepreneurial intentions between students under 20 and those aged above 20. Likewise, there was no difference of entrepreneurial intentions  between students whose parents were entrepreneurs and those whose parents were non-entrepreneurs.